Anisotropic surface texturing of silicon substrate using alkaline solution for solar cell application - Vacalares, Kayrol Ann B. (Transactions of the National Academy of Science and Technology, 2011)
High-efficiency silicon solar cells need a textured front surface to reduce the reflectance of incident light and to improve light trapping using cost-effective method. In this work, we report on the anisotropic surface texturing of Si(100) substrates using alkaline solution, forming pyramidal structures on its front surface. This method provides a straight forward and cost-effective approach. We utilized a mirror-polished single crystalline Si(100) substrate for texturing using alkaline solution. The alkaline mixtures contained sodium hydroxide, isopropyl alcohol and de-ionized water. The concentration of the alkaline solution was held constant while varying the texturing time. The surface morphology of the textured surface is investigated by Scanning Electron Microscope (SEM) and its reflectance is measured using UV-Vis Spectrometer. Results showed that the sizes and shapes of the resulting pyramids after texturing process are dependent on the texturing time. Furthermore, the pyramid density increases with increasing etching time. Moroever, SEM images revealed that the size and uniformity of the pyramids affect the reflectance of the incident light as dejected in the UV-Vis spectra of the mirror-polished and textured silicon samples. It was found that reflectance of the incident light could be reduced up to less than 20% by optimizing the surface morphology of the textured silicon. It is suggested that having a large and almost uniformly distributed pyramids on the Si surface will drastically reduce the reflectivity. We also present in this study a model that will describe and discuss the effects on the reflectance in relation to the distribution of pyramids in terms of distance and size.